Colonizing Russia's Promised Land : Orthodoxy and Community on the Siberian Steppe - Friesen, Aileen, 1980- (Book collections on Project MUSE., 2020)
"The movement of millions of settlers to Siberia in the late nineteenth and early twentieth centuries marked one of the most ambitious undertakings pursued by the tsarist state. Colonizing Russia's Promised Land examines how Russian Orthodoxy acted as a basic building block for constructing Russian settler communities in current-day southern Siberia and northern Kazakhstan. Russian state officials aspired to lay claim to land that was politically under their authority, but remained culturally unfamiliar. By exploring the formation and evolution of Omsk diocese--a settlement mission--Colonizing Russia's Promised Land reveals how the migration of settlers expanded the role of Orthodoxy as a cultural force in transforming Russia's imperial periphery by "russifying" the land and marginalizing the Indigenous Kazakh population."--